Unsettling Responsibility in Science Education Indigenous Science, Deconstruction, and the Multicultural Science Education Debate - Higgins, Marc (Palgrave Studies in Educational Futures, 2021)
"Moving beyond tropes of empowerment, scientific literacy, and related bon hommes, Higgins's book offers one of the richest theoretical assemblages I have read in some time. He welds insights from post-humanist, feminist, Indigenous, and post-colonial scholars, conducing the theoretical potential of being and becoming into a fleshed out educational experience." -Kent den Heyer, Professor of Education, University of Alberta, Canada "Exploring the relationships between Indigenous and Western Science in science education, this book takes readers on a journey which explores various converging and diverging theoretical and epistemological standpoints that challenge normalized binary ways of looking at the world." -Eun-Ji Amy Kim, Lecturer, School of Education and Professional Studies, Griffith University, Australia This open access book engages with the response-ability of science education to Indigenous ways-of-living-with-Nature. Higgins deconstructsthe ways in which the structures of science education-its concepts, categories, policies, and practices-contribute to the exclusion (or problematic inclusion) of Indigenous science while also shaping its ability respond. Herein, he undertakes an unsettling homework to address the ways in which settler colonial logics linger and lurk within sedimented and stratified knowledge-practices, turning the gaze back onto science education. This homework critically inhabits culture, theory, ontology, and history as they relate to the multicultural science education debate, a central curricular location that acts as both a potential entry point and problematic gatekeeping device, in order to (re)open the space of responsiveness towards Indigenous ways-of-knowing-in-being.